HEM VEJAKORN : LIFE AND WORKS IN THAI IDENTITY - Thimwatbunthong, Sathit (Srinakharinwirot Research and Development Journal of Humanities and Social Sciences, 2024)
The objective of this research is to study the development of Thai Contemporary Art through the study of Hem Vejakorn’s life, experiences, and works using documentary research methodology. The research criteria are: 1) the concepts in the stories and forms that show Thai Identity and 2) the principles, composition and the use of color. It is found that Hem Vejakorn did not pursue his art knowledge conventionally. His first art teacher was an Italian painter name Carlo Rigoli. Hem came from a broken family but he was extremely gifted. His works impressed and were widely praised by the public. His Majesty King Rama IX was greatly impressed by his work and Hem became an artist under the royal patronage. The lists of the pictures used in this research are as follows: 3 illustrations from SunthornPhu’s autobiography: I Watch the World in Sorrow; In Poverty, There Wasn’t Even One Place I Can Live and The Taste of Life. 6 illustrations of the heroines from the following stories: Pimpilalai, Khaki, Kraithong, Matsee, PraPuenPra Pang, and Rotjana.Thai Ghosts. I Already Stop. When Will You? When Life Flows by Like a Song. These illustrations are the representatives of his whole works, which are around forty thousand pictures. Although they were just illustrations in the newspapers and books back then, they are highly treasured and valued today. From an ordinary person, Hem Vejakorn has created the masterpieces that are valuable to the art world. His “mere illustrations” have transcended time and have become the priceless works of art that reflect limitless ideas and imagination.